ICT / GRM relationship: Case of AGB bank - Tlemcen - GRARI, Yamina; AMERANI, Meriem (Dirassat Journal Economic Issue, 2016)
This paper supports the analytical study of the issues raised regarding the relationship that may exist between the use of information and communication technologies and customer relationship management. In this context, We took Algeria Gulf Bank as a case study from the province of Tlemcen in order to show the importance of ICT within the Bank in order to build customer loyalty in the long term.